The Brassica napus phytoglobin 1 (BnPgb1) mitigates the decrease in plant fertility resulting from high temperature stress - Ibrahim, Shimaa (Journal of plant physiology, 2024)
Copyright © 2024 Elsevier GmbH. All rights reserved.